PENGEMBANGAN MEDIA PEMBELAJARAN BUKU CERITA BERGAMBAR BERBASIS FIKSI MATA PELAJARAN BAHASA DAERAH MAKASSAR KELAS 3 DI SD INPRES LAKIYUNG - Riswandi; Abdul Hakim; Farida Febriati (STKIP Subang, 2026)
The purpose of this study was to describe the needs, develop a product design, and test the validity and practicality of a multilingual fiction-based picture storybook (Makassar and Indonesian) learning media featuring Lontara script for third-grade students. This study used a Research and Development (R&D) approach, applying the 4-D development model (Define, Design, Develop, Disseminate). The study subjects consisted of 20 third-grade students, one homeroom teacher, and two expert validators. Data collection instruments included a needs analysis questionnaire, a validation sheet, and a user response questionnaire. The results showed that the content expert's level of validity reached a very good level with a percentage of 100%, while the media expert's level of validity reached a good level with a percentage of 82%. In the practicality test, responses from students reached 92% and responses from homeroom teachers reached 100%, both of which fall into the very practical category. The conclusion of this study shows that the fiction-based picture story book learning media developed is valid, very practical, and effective to use as a fun supporting media as well as being a concrete effort in preserving the Lontara Makassar script culture for students.